The Development of Autopilot System for an Autonomous UAV Helicopter Model - Wahab, A. A. (2006)
This paper presents the design decision and development of autopilot system for an autonomous unmanned aerial vehicle (UAV) helicopter model. The autopilot system designed to demonstrate autonomous maneuver such as take-off, hover and forward flight. The overall system consists of the helicopter with an on-board computer and a second computer serving as a ground station. The flight control is done on-board while mission planning and human user interaction takes place on ground. Sensors used for autonomous operation include acceleration, magnetic field, and rotation sensors (Attitude and Heading Referance System) and ultrasonic transducers. The hardware and software used to autonomously pilot the helicopter are described in detailed in this paper.